Reconstruction of the Regulation for the Execution of State-Owned Enterprises (BUMN) Persero Declared Bankruptcy Based on the Values of Justice - Wibowo, Moh. Bekti; Mashadurohatun, Anis; Purnawan, Amin (Indonesian Journal of Advanced Research, 2025)
This study aims to analyze the implementation of the execution of SOEs in the form of Persero that were declared bankrupt, identify weaknesses in existing regulations, and reconstruct these regulations based on the value of justice. Using the constructivism paradigm with a socio-legal research approach, this study is descriptive and uses secondary data. The results of the study show that the execution regulations for bankrupt Persero SOEs still have fundamental weaknesses in terms of substance, structure, and legal culture, especially related to the protection of state assets and legal certainty. It was found that there was a disharmony between the Bankruptcy Law and a number of other laws. Therefore, a regulatory reconstruction based on the value of justice is needed to ensure the protection of state assets and legal certainty in the bankruptcy of Persero SOEs that carry out public functions.